Way of Unity, Way of Holiness - Monti, Emilio N. (International review of mission, 1999)
We have all become neighbours in a ‘global village’, black and white, rich and poor, Christian, Muslim, Buddhist, followers of other faiths or atheists. Torn by our differences and tensions we still do not know how to live together in a world where we are bound to live together as one community.